Stress among police officials in Kerala, India: an analysis of organizational and operational factors - Mini GK; Chitra Venkateswaran; Anjana VM; Sangeeth Krishna S; Greeshma J; Greeshma PS; Revathy K; Vilma Irazola; John Romate (BMC Psychology)
Abstract Background Globally, the rising concern regarding the stress experienced by police officials poses a significant challenge. However, there is limited research on this issue in low- and middle-income countries like India. The present study examines the specific stressors associated with the operational demands and organizational structures experienced by police officers in the state of Kerala, India. Methods A survey was conducted among police officials working in randomly selected police stations located in the Thiruvananthapuram district, Kerala. We used the level of occupational and organizational stress using the police stress questionnaire. Both bivariate and multivariate logistic regression analyses were employed to determine the factors that were associated with higher stress levels. Results The findings indicated that 75.5% of participants experienced high operational stress and 65.6% experienced high organizational stress. Age was significantly associated with operational stress, with participants in the higher age group reporting higher levels of stress(odds ratio (OR): 2.20, 95% confidence interval (CI): 1.05–4.59). Participants with lower physical activity levelshad a higher likelihood of experiencing operational stress (OR: 7.07; CI: 2.85–17.50) and organizational stress (OR: 2.77, 95% CI: 1.38–5.59) compared to their more active counterparts. The use of alcohol or tobacco was found to be the highest associated factor with operational (OR: 14.58, CI:4.19–50.7) and organizational stress (OR: 27.45, CI:8.01–94.03). Having diabetes or hypertension was also significantly associated with a high level of operational stress (OR: 2.97, CI: 1.32–6.60) and organizational stress (OR: 4.16; CI: 2.02–8.57). Conclusions The study highlights factors associated with higher stress levels, including physical inactivity, alcohol or tobacco use, and morbidity, that require targeted interventions to enhance the mental and physical health of police officers. Based on the findings of the study, the researchers proposesuitable intervention programs in this population. Further, the findings suggest that the police departments may consider providing better stress-management skills, mental health resources, and flexible work arrangements to managestress.